ШАХС ХУСУСИЯТИНИ ИФОДАЛОВЧИ РУСЧА ЎЗЛАШМА ИБОРАЛАРНИНГ СЕМАНТИК ХУСУСИЯТЛАРИ - Абдиев, М. (SCIENCE and SOCIETY, 2019)
The article is devoted to the analysis of Russian phraseological units used in the Uzbek language. The questions of the process of reciprocal phraseological units in Uzbek linguistics were also investigated.
Keywords: phraseological unit; native layer; mutual layer; tracing-paper; tracing; translation; process; borrowed word; vocabulary; grammatical structure; lexeme; spoken language